Regeneration Patterns following Regeneration Felling in Sal (Shorea robusta Gaertn.f.) Forests Managed under the Shelterwood System - Thakur, Ram Bichari; Rai, Rajesh Kumar; Pokharel, Ridish Kumar; Neupane, Prem Raj (Banko Janakari, 2025)
A shelterwood system was implemented, with regeneration felling carried out in the most degraded areas and mother trees retained to support seedling establishment. Empirical findings indicate high regeneration density but low species richness. Additionally, concerns remain regarding the quality of regeneration, including the origin of seedlings following regeneration felling. In this context, this study examines regeneration dynamics in six community-managed Sal (Shorea robusta) forests in Nepal’s far-western region, where dry climatic conditions and forest fragmentation pose significant challenges to regeneration. A total of 376 sample plots were surveyed, with managed plots (subjected to regeneration felling) compared to natural stands. Seedling and sapling densities were assessed using systematic sampling, and a semi-destructive method was employed to determine the origin of seedlings (seed vs. seedling coppice). The findings revealed that managed plots had significantly higher density and species richness across both seedling and sapling stages of regeneration. Seedling coppice dominated both managed and natural stands, with significantly higher seed-originated seedlings in natural stands. Overall, the study highlights the effectiveness of regeneration felling under a shelterwood system, which enhances regeneration density and species richness, and improves the mechanical properties of wood by promoting seed-originated seedlings.